Sedimentation pattern of kame terraces and its implication to climatic events in the Gangotri glacier region since 25 Ka BP, Garhwal Himalaya, India. (15th May 2022) - Dubey, Chetan Anand; Singh, Dhruv Sen; Singh, Anoop Kumar; Sangode, Satish Jagdeo; Kumar, Dhirendra; Kumar, Pankaj
Graphical abstract: Highlights: The sedimentation in the Kame terraces has taken place under low energy stagnant water conditions in a lacustrine environment. The Kame terraces were evolved under glacial-fluvial at the base and lacustrine environment at the top. The study demonstrates climate change since 25 Ka BP. The study confirms the major climatic signatures such as Last Glacial Maximum, Older Dryas, Bølling-Allerød, Younger Dryas, Indus Valley Civilization Collapse, Medieval Warm Period and Little Ice Age. Abstract: Gangotri glacier, located in the Uttarkashi district, is one of the longest valley glaciers of the Garhwal Himalaya. It exhibits lateral moraines, recessional moraines, outwash plains, kame terraces, and debris cones. Kame terraces are significant landforms that preserve the climatic records and geological history in their deposits. The sedimentary and mineral magnetic analysis on 165 cm thick trenched sections sampled at 2.5 cm interval of the kame terraces together with the AMS (Accelerator Mass Spectrometer) age indicate its response to the major climatic events in this region and sedimentation history of the kame terraces. The granulometric analysis describes that the mean grain size of these sediments varies from coarse to fine sand, which are poorly sorted with an excess of finer sediments. This indicates, low to moderate energy over a longer duration with fluctuation of the depositional environment. The mineral magnetic analysis reflects unimodal detrital modes governed by the energy conditions from meltwaters that are in turn controlled by the climatic conditions from warmer to colder episodes. Therefore, the sedimentation in the kame terraces has taken place under the low energy lacustrine environment during warmer climates. The kame terraces sedimentation therefore has recorded the major climatic events, such as Last Glacial Maximum (LGM) 21–19.5 Ka BP, Older Dryas (OD) 16.5–14.5 Ka BP, Bølling-Allerød (BA) 14.5–13.5 Ka BP, Younger Dryas (YD) 13.5–12 Ka BP, Indus Valley Civilization Collapse (IVCC) 5.0–3.0 Ka BP, Medieval Warm Period (MWP) 1.25–0.7 Ka BP and Little Ice Age (LIA) 0.7–0.2 Ka BP.